Hubungan Tingkat Pengetahuan Kesehatan Reproduksi Remaja dengan Sikap Seksual Pranikah di SMK Taman Siswa Nanggulan Tahun 2017 - Putri Handhika; Suherni Suherni; Sumarah Sumarah (Poltekkes Kemenkes Yogyakarta, 2017)
The number of adolescents in Indonesia is estimated to have reached 62 million people. The current problem of reproductive healthknowledge is so complex that it is demonstrated in the outcomes of the 2012 KRR SDKI that adolescent knowledge of reproductivehealth is inadequate, which can be seen by only 35.3% of female adolescents and 31.2% of boys aged 15- 19 years of knowing thatwomen can get pregnant with one sexual intercourse. The purpose of this research is to know the correlation of knowledge ofadolescent reproduction health with premarital sexual attitude at SMK Taman Siswa Nanggulan in 2017. This Research Method isAnalytical Survey, research type using Observasional with cross sectional time approach, sampling using purposive sampling that isused subject in the case of 80 adolescents The number of samples was determined by using different proportional hypothesis test(Lemeshow 1997) The minimum sample found for this study was 72 respondents plus 10% to become 80 respondents. Datacollection used questionnaires distributed to respondents, analyzed using univariate and bivariate analysis using chi-squareanalysis. The results of the study there is a significant relationship between knowledge of adolescent reproductive health withpremarital sexual behavior, p-value 0.000. This research can be concluded that there is correlation of level of knowledge ofreproductive health of adolescent significant with premarital sexual attitude.